Immune Checkpoint Inhibitors in Melanoma: Review and Update - Eugénia Matos Pires; Cecília Moura (Sociedade Portuguesa de Dermatologia e Venereologia, 2018)
The overall increasing incidence of melanoma will very probably be the trend over the next two decades. This data stresses the need for new therapeutic resources, other than classic chemotherapy. Nevertheless, the treatment of advanced melanoma has been changed in the last decade due to novel therapeutic strategies, including immunotherapy with immune checkpoint inhibitors targeting cytotoxic T lymphocyte-associated protein 4 (CTLA-4) and programmed cell death protein 1 (PD-1). Inhibition of these targets enhances immune host response against cancer and results in durable objective responses, establishing immunotherapy as standard treatment for BRAF wild-type melanoma patients in advanced stages (III - unresectable and IV - metastases at distant sites). Anti-CTLA-4, ipilimumab, was the first-in-class immune checkpoint inhibitor to show improvement in overall survival in advanced melanoma. Latter, anti-PD-1 agents, nivolumab and pembrolizumab, have improved tumour response and tolerability in comparison with ipilimumab. Differences in outcome are expected considering the distinct target of checkpoint inhibition pathways. In this setting, it is of utmost importance the assessment of efficacy by combined therapy and the identification of biomarkers capable of predicting response to anti-CTLA-4 and anti-PD-1. After a previous review on cancer biology and mechanisms of action of immune checkpoint inhibitors we will focus on the main data on the immune checkpoint inhibitors for melanoma currently available in daily practice.